2022
DOI: 10.14245/ns.2244750.375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Subsidence on Segmental and Global Lordosis at Long-term Follow-up After Anterior Cervical Discectomy and Fusion

Abstract: Objective: Subsidence following anterior cervical discectomy and fusion (ACDF) may lead to disruptions of cervical alignment and lordosis. The purpose of this study was to evaluate the effect of subsidence on segmental, regional, and global lordosis.Methods: This was a retrospective cohort study performed between 2016–2021 at a single institution. All measurements were performed using lateral cervical radiographs at the immediate postoperative period and at final follow-up greater than 6 months after surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…These results highlight the relevance of addressing the best surgical practices in order to avoid subsidence. Even if the measurement of cervical and segmental lordosis was above the scope of this case series, this finding can be explained by the fact that subsidence after ACDF produce a loss of segmental lordosis [31]. Since a lower C2-C7 Cobb angle and kyphotic deformity are related with higher disability [10], the subgroup of patients which suffered from subsidence in our study may have reached a degree of loss of segmental lordosis which produced a worse pain and disability outcome.…”
Section: Discussionmentioning
confidence: 60%
“…These results highlight the relevance of addressing the best surgical practices in order to avoid subsidence. Even if the measurement of cervical and segmental lordosis was above the scope of this case series, this finding can be explained by the fact that subsidence after ACDF produce a loss of segmental lordosis [31]. Since a lower C2-C7 Cobb angle and kyphotic deformity are related with higher disability [10], the subgroup of patients which suffered from subsidence in our study may have reached a degree of loss of segmental lordosis which produced a worse pain and disability outcome.…”
Section: Discussionmentioning
confidence: 60%
“…However Zhe et al 15 revealed that the overall subsidence rate was higher in the ZPSC implants than in the CCP implants (66.67% vs 38.46%, p = 0.006). In a meta-analysis conducted by Yingjje 35 ZPSC implants had a higher incidence of postoperative subsidence than that in the CCP implants (15.1% vs 8.8%, p = 0.0005). Our study confirmed prior findings that using a ZPSC implant without a plate leads to a higher subsidence rate, interfering with disc stability and potentially incurring a higher reoperation rate 5 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 90%
“…However, more proper patient selection and technical modifications such as over-milling of the endplate’s avoidance enabled the Bryan prosthesis to overcome this default [ 40 ]. Even ACDF also has the concerns of segmental kyphotic change, further leading to worse clinical outcomes, associated with subsidence of intervertebral cages [ 41 ].…”
Section: Discussionmentioning
confidence: 99%